Financial Literacy, Lifestyle, and Financial Behavior Among Generation Z: The Moderating Role of Siri’ Local Wisdom - Asriany; Rikinorhakis Ridzwan; Antong; Riyanti; Samsul Bachri; Andi Jaman (Fundamental and Applied Management Journal, 2026)
This study examines the effects of financial literacy and lifestyle on financial behavior among Generation Z and tests whether Siri’ Culture functions as a cultural moderator. A quantitative correlational design was employed using data from 203 Generation Z respondents domiciled in Palopo City, South Sulawesi, Indonesia. The respondents were selected from the defined Generation Z population and data were collected through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares with SmartPLS 4.0. The findings reveal that financial literacy has a significant positive effect on financial behavior, indicating that respondents with higher financial knowledge tend to demonstrate more responsible financial management practices. In contrast, lifestyle does not significantly influence financial behavior. Siri’ Culture also does not significantly affect financial behavior either directly or as a moderating variable in the relationships between financial literacy, lifestyle, and financial behavior. These findings indicate that financial literacy remains the strongest determinant of financial behavior in this sample, while the null results for Siri’ Culture suggest that indigenous cultural values may not automatically translate into measurable financial behavior effects unless activated through specific social, educational, or institutional mechanisms. This study contributes to behavioral finance by clarifying the boundary conditions for integrating indigenous cultural values into quantitative financial behavior models.